Natural capital accounting in the context of the socio-economic paradigm of financial reporting: conceptual and methodological aspects - Golochalova, Irina; Vakun, Oksana (Public Policy and Accounting, 2020)
In the context of ensuring sustainable development, the activities of a business entity have come to be viewed as a three-component system designed to provide reliable information on the contribution of business to the social and environmental segments of the economy. This trend has led to the transition to the financial reporting socio-economic paradigm, which predetermines its revolutionary transformations, one of which is finding ways to recognize natural capital and disclose information about its impact on the business entity’s value. In the article the conceptual foundation for the recognition of natural capital and impact of its disclosure in financial statements on the business entity’s value has been provided. The methodological aspects of the recognition of two forms of natural capital (natural resources and ecosystem services) have been analyzed. The generalized model for the recognition of natural capital based on the IFRS system has been proposed. The system of accounting and financial reporting of the Republic of Moldova in the context of the transition to the socio-economic concept of disclosing information about the business entity’s value has been characterized.